μVEMP: A Portable Interface to Record Vestibular Evoked Myogenic Potentials (VEMPs) With a Smart Phone or Tablet - MacDougall, Hamish G.; Holden, John; Rosengren, Sally M.; Chiarovano, Elodie (Frontiers in Neurology, 2018)
Background Cervical VEMPs and ocular VEMPs are tests for evaluating otolith function in clinical practice. We developed a simple, portable and affordable device to record VEMP responses on patients, named μVEMP. Our aim was to validate and field test the new μVEMP device. Methods We recorded cervical VEMPs and ocular VEMPs in response to bone conducted vibration using taps tendon hammer to the forehead (Fz) and to air conducted sounds using clicks. We simultaneously recorded VEMP responses (same subject, same electrode, same stimuli) in three healthy volunteers (2 females, age range: 29-57 years) with the µVEMP device and with a standard research grade commercial (CED) system used in clinics. We also used the µVEMP device to record VEMP responses from six patients (6 females, age mean±SD: 50.3±20.8 years) with classical peripheral audio-vestibular diseases (unilateral vestibular neuritis, unilateral neurectomy, bilateral vestibular loss, unilateral superior canal dehiscence, unilateral otosclerosis). Results The first part of this paper compared the devices using simultaneous recordings. The average of the concordance correlation coefficient was rc = 0.997±0.003 showing a strong similarity between the measures. VEMP responses recorded with the µVEMP device on patients with audio-vestibular diseases were similar to those typically found in the literature. Conclusion We developed, validated and field tested a new device to record ocular and cervical VEMPs in response to sound and vibration. This new device is portable (powered by a phone or tablet) with pocket-size dimensions (105x66x27mm) and light weight (150 grams). Although further studies and normative data are required, our µVEMP device is simpler (easier to use) and potentially more accessible (more affordable) than standard, commercially available equipment.